A Patient with Difficulty of Object Recognition: Semantic Amnesia for Manipulable Objects - A. Yamadori; Y. Yoneda; H. Yamashita; K. Sugiura (Behavioural Neurology)
We studied a patient who had recognition difficulty for manipulable objects. MRI showed a lesion in the left occipito-parietotemporal area. Differential diagnosis of agnosia, aphasia and apraxia is discussed. We believe this “object meaning amnesia” constitutes a distinct subtype of semantic amnesia.